Cover Image, Volume 39, Number 6, September 2022. Issue 6 (29th July 2022) - Lee, Shawndy M.; Ng, Wei H.; Tang, Emmanuel; Foong, Shaohui
Abstract : The cover image is based on the Research Article Towards fluid force estimation of a water‐jetting aerial robot with hybrid kinematics‐force model by Shawndy M. Lee et al., https://doi.org/10.1002/rob.22079 .